Ethnic Diversity and Pathways to Care for a First Episode of Psychosis in Ontario - Archie, S. (Oxford University Press, 2010)
Objective: To examine ethnic variations in the pathways to care for persons accessing early intervention (EI) services in Ontario. Method: The pathways to care and the duration of untreated psychosis were assessed for first-episode psychosis patients who entered specialized EI services in Ontario. The sample was assigned to the following ethnic classifications: the White (Caucasian), Black (African descent), and Asian (ancestry from the continent) groups, plus all the “other ethnicities” group. Results: There were 200 participants: 78% were male; 61% from the White, 15% Black, 13% Asian, and 11% were from the other ethnicities group. At the first point of contact, more participants used nonmedical contacts (12%), such as clergy and naturopathic healers, than psychologists (8%) or psychiatrists (7%). There were no ethnic differences for duration of untreated psychosis (median 22 weeks) or for initiation of help seeking by family/friends (53%), police (15%), or self (33%). After adjusting for relevant clinical and demographic factors, the Asian and other ethnicities groups were 4 and 3 times (respectively) more likely than the White or Black groups (P = .017) to use emergency room services as the first point of contact in the pathways to care. Participants from the Asian group experienced less involuntary hospitalizations (P = .023) than all the other groups. Yet overall, there were many more similarities than significant differences in the pathways to care. Conclusion: EI services should monitor the pathways to care for young people of diverse ethnic backgrounds to address any disparities in accessing care.